Spatial Analysis of Pneumonia in Toddlers Based on Environmental, Individual, and Behavior Factors in Pelalawan Regency, Riau Province - Yessi Harnani1 , Rasoel Hamidy1 , Sukendi1 , Dedi Afandi1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Pelalawan Regency is one of twelve districts in Riau Province with pneumonia cases in toddlers is quitehigh, namely in 2016 there were 155.7% of pneumonia cases in toddlers. Based on these cases, there isno clear information on how the cases were spread related to environmental risk factors. The researchaims to conduct spatial pneumonia analysis in toddlers based on environmental, individual and behavioralfactors. By knowing the pattern of disease distribution and its possible causes, it will be easier for officers toplan pneumonia prevention efforts and prevention more effectively, community-based or make it easier todesign the development of further prevention programs. This research is a survey research with quantitativeanalytic methods conducted in 12 Districts of Pelalawan Regency, Riau Province. The results showed thehighest distribution of pneumonia frequency in toddlers by region in 12 Districts of Pelalawan District wasthe highest in Districts of Pelalawan.